World Englishes Implications for international communication and english language teaching - Kirkpatrick, Andy (Cambridge University Press, 2014)
The model of English that should be used in classrooms has long been a subject of debate. World Englishes, Implications for International Communication and English Language Teaching, (with an accompanying audio CD) describes selected varieties of World Englishes, and discusses the advantages and disadvantages of selecting a particular variety from the point of view of both teachers and learners. It aims to examine and re-evaluate concepts such as 'standard', 'variety', 'native speaker' and 'non-native speaker', and to validate the role played by multilingual and multicultural English language teachers, arguing that context and learner needs should determine the variety to be taught. World Englishes was shortlisted for the 2008 British Council Innovations Awards.